Трансформація банківських послуг в умовах цифровізації - Цибенко, Олег Михайлович; Tsybenko, Oleh Mykhaylovych (Ірпінь, 2024)
Розглянуто цифровізацію як основу створення об’єктивних передумов для трансформації банківських послуг. Здійснено класифікацію банківських послуг та дослідити їх цифрову трансформацію. Проаналізовано еволюцію процесів інформатизації та цифровізації банківських послуг в Україні. Розглянуто технологічні інновації як основу трансформації банківських послуг. Оцінено стан впровадження Інтернет-банкінгу, відкритого банкінгу та штучного інтелекту в Україні. Визначено перспективні напрями прискорення трансформації банківських послуг в умовах цифровізації.

Digitization is considered as the basis for creating objective prerequisites for the transformation of banking services. The classification of banking services was carried out and their digital transformation was investigated. The evolution of the processes of informatization and digitization of banking services in Ukraine is analyzed. Technological innovations are considered as the basis of the transformation of banking services. The state of implementation of Internet banking and open banking was evaluated and artificial intelligence in Ukraine. Prospective directions for accelerating the transformation of banking services in conditions of digitalization have been identified.
Transformation of banking services in conditions of digitalization
Keywords: трансформація; цифровізація; банківські послуги; банки; інформатизація; комп’ютеризація; Інтернет-банкінг; відкритий банкінг; штучний інтелект; transformation; digitalization; banking services; banks; informatization; computerization; Internet-banking; open banking; artificial intelligence